2016
DOI: 10.1007/s11695-016-2419-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Vagal Nucleus Tractus Solitarius in the Therapeutic Effects of Obesity Surgery and Other Interventional Therapies on Type 2 Diabetes

Abstract: The current treatment for obesity-related type 2 diabetes is not able to achieve sufficient metabolic control. New remission prospects have been offered through bariatric surgery and other interventional therapies. The aim of the study is to illustrate the mechanism by which such therapies affect the autonomic system, in particular the afferent vagal activity. The first and most important terminal of this activity is the brainstem vagal nucleus tractus solitarius. Its function, on which the vagal efferent inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 130 publications
1
11
0
Order By: Relevance
“…On the other hand, GLP-1, a potent anorectic and incretin, has emerged as a promising treatment for both obesity and diabetes mellitus (Näslund et al, 2004 ). And Blasi has emphasized the importance of the area postrema and the vagal nucleus tractus solitarius in restoring normal function to the pancreas, liver, and gastrointestinal tract following bariatric surgery (Blasi, 2016 ). ; it is no coincidence that this same medullary region plays a major role in transducing orexigenic signals from ghrelin and anorexigenic signals from BDNF, GDF15, and the intestinal hormones GLP-1, cholecystokinin, amylin, PP, and PYY (Wren, 2008 ; Clemmensen et al, 2017 ); see Table 1 and Figure 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, GLP-1, a potent anorectic and incretin, has emerged as a promising treatment for both obesity and diabetes mellitus (Näslund et al, 2004 ). And Blasi has emphasized the importance of the area postrema and the vagal nucleus tractus solitarius in restoring normal function to the pancreas, liver, and gastrointestinal tract following bariatric surgery (Blasi, 2016 ). ; it is no coincidence that this same medullary region plays a major role in transducing orexigenic signals from ghrelin and anorexigenic signals from BDNF, GDF15, and the intestinal hormones GLP-1, cholecystokinin, amylin, PP, and PYY (Wren, 2008 ; Clemmensen et al, 2017 ); see Table 1 and Figure 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In his review of the therapeutic effects of obesity surgery, Blasi notes the rapid and often persistent remission of type 2 diabetes and the metabolic syndrome following bariatric surgery, and reviews the major role that the vagal NTS and vaso-vagal pathways play in restoring normal function to the pancreas (normalizing insulin secretion, reducing glucagon production), liver (recovering insulin sensitivity, reducing gluconeogenesis and free fatty acid release), and gastrointestinal tract (reducing ghrelin secretion, restoring normal responses to nutrients, peptides, hormones) (Blasi, 2016 ).…”
Section: Obesity and Metabolic Homeostasismentioning
confidence: 99%
“…The deterioration of the synaptic connection with the DMV (synaptic maladaptation) leads to a disordered modulation of the splanchnic organs with their consequent dysfunction (altered production of insulin and glucagon, and impaired hepatic synthesis and release of glucose) [47].…”
Section: Role Of the Brainstem And The Gut-brain Axismentioning
confidence: 99%
“…23 In obesity and T2DM, this gut-brain axis is dysfunctioning. 24 Additionally, it has been observed that a high-fat diet and T2DM correlate with presence of neuropathy in the duodenal myenteric plexus, a decrease in the supporting enteric glial cells, and the loss of duodenal neurons. 25 Recovery of these neuronal pathways can be achieved; it has been suggested that both RYGB and vertical sleeve gastrectomy lead to improved energy homeostasis and metabolism by manipulation of vagal afferent fibers of the ENS.…”
Section: The Duodenum Is Densely Innervated By the Nervous Systemmentioning
confidence: 99%
“…25 Recovery of these neuronal pathways can be achieved; it has been suggested that both RYGB and vertical sleeve gastrectomy lead to improved energy homeostasis and metabolism by manipulation of vagal afferent fibers of the ENS. 24 Duodenal interventions and their effects could greatly help to unravel the gut-brain axis in humans and could lead to unexpected treatment modalities.…”
Section: The Duodenum Is Densely Innervated By the Nervous Systemmentioning
confidence: 99%